Ion dynamics in methylcellulose–LiBOB solid polymer electrolytes - Yusof, S.Z.; Woo, H.J.; Arof, Abdul Kariem (Springer Verlag, 2016)
A polymer electrolyte system comprising methylcellulose (MC) as the host polymer and lithium bis(oxalato) borate (LiBOB) as the lithium ion source has been prepared via the solution cast technique. The electrolyte with the highest conductivity of 2.79 μS cm−1 has a composition of 75 wt% MC–25 wt% LiBOB. The mobile ion concentration (n) in this sample was estimated to be 5.70 × 1020 cm−3. A good correlation between ionic conductivity, dielectric constant, and free ion concentration has been observed. The ratio of mobile ion number density (n) at a particular temperature to the concentration n0 of free ions at T = ∞ (n/n0) and the power law exponents (s) exhibit opposite trends when varied with salt concentration.